Spectral analysis of intraocular pressure pulse wave in ocular hypertensive and primary open angle glaucoma patients - Bozic, Marija M (Indian J Ophthalmol, 2016)
CONTEXT: In attempt to find an alternative way to determine conversion from ocular hypertension to primary open angle glaucoma (POAG) (besides visual field and optic disc changes), we analyzed intraocular pressure (IOP) pulse wave in spectral domain. AIMS: The aim of this study was to test the potential differences in spectral content of IOP pulse wave between ocular hypertension and POAG patients, which could indicate conversion. SETTINGS AND DESIGN: Cross-sectional study designed to test the differences in the spectral content of pressure pulse wave between nontreated ocular hypertensive and nontreated, freshly diagnosed POAG patients. METHODS: The total of 40 eyes of 40 subjects was included: 20 previously untreated ocular hypertensive patients, and 20 previously untreated POAG patients. Continuous IOP measuring gained by dynamic contour tonometry was submitted to fast Fourier transform signal analysis and further statistical data processing. STATISTICS ANALYSIS USED: Ocular and systemic characteristics of the tested subjects were compared by analysis of variance appropriate for this study design. A P < 0.05 was considered to be statistically significant. RESULTS: Higher spectral components of the IOP pulse wave was discerned up to the fifth harmonic in both of the tested groups. No statistically significant differences were found in any of the tested harmonic amplitudes. CONCLUSIONS: There are no differences in the spectral content of IOP pulse wave between ocular hypertensive and primary open angle glaucoma patients which could be indicative for conversion.